Histology of the mantle and pearl-sac formation in the Indian pearl oyster Pinctada fucata (Gould) - Velayudhan, T S; Chellam, A; Dharmaraj, S; Victor, A C C; Alagarswami, K (Indian Journal of Fisheries, 2011)
The epithelial cells and the associated secretory cells in different regions of the mantle exhibited modifications according to their functions. The pearl-sac formation under laboratory conditions, histology of the mantle and the pearl-sac of P. fucata (Gould) are detailed here.